Communicative aspects of terrorism and radicalization in the digital age of global media - Marković Branko S. (Baština)
Terrorist act as a result of complex forms of action of individuals and groups cannot be fully accomplished in the modern world without generating its publicity. That is why terrrorist activities are thoughtfully adapted to modern means of mass media in order to realize political violence strategies and promote radical ideologies. To this effect, a terrorist act has its own real and media-symbolic dimension. The real dimension of terrorist act is defined by immediate terrorist activities, while the media dimension of the terrorist act (mediated by mass media) is ambiguous symbolic message that finds its meaning only in the terrorist narrative. Radicalization as a process is inseparably connected to spreading and promoting these ideas. On the other hand, the media focused on violence and sensationalism, under pressure to be the first in reporting, voluntarily and involuntarily encourage terrorism and counterterrorist activities. However, the symbiosis between mass media and terrorism has a positive dimension realized through expanding the narrative against terrorism in the process of preventing radicalization.